Acteoside and ursolic acid synergistically protects H2O2-induced neurotrosis by regulation of AKT/mTOR signalling: from network pharmacology to experimental validation - Yan-Jie Qu; Min-Rui Ding; Chao Gu; Li-Min Zhang; Rong-Rong Zhen; Jin-Fang Chen; Bing Hu; Hong-Mei An (Taylor & Francis Group, 2022)
Context Ursolic acid (UA) and acteoside (ATS) are important active components that have been used to treat Alzheimer's disease (AD) because of their neuroprotective effects, but the exact mechanism is still unclear.Objective Network pharmacology was used to explore the mechanism of UA + ATS in treating AD, and cell experiments were used to verify the mechanism.Materials and methods UA + ATS targets and AD-related genes were retrieved from TCMSP, STITCH, SwissTargetPrediction, GeneCards, DisGeNET and GEO. Key targets were obtained by constructing protein interaction network through STRING. The neuroprotective effects of UA + ATS were verified in H2O2-treated PC12 cells. The subsequent experiments were divided into Normal, Model (H2O2 pre-treatment for 4 h), Control (H2O2+ solvent pre-treatment), UA (5 μM), ATS (40 μM), UA (5 μM) + ATS (40 μM). Then apoptosis, mitochondrial membrane potential, caspase-3 activity, ATG5, Beclin-1 protein expression and Akt, mTOR phosphorylation levels were detected.Results The key targets of UA + ATS-AD network were mainly enriched in Akt/mTOR pathway. Cell experiments showed that UA (ED50: 5 μM) + ATS (ED50: 40 μM) could protect H2O2-induced (IC50: 250 μM) nerve damage by enhancing cells viability, combating apoptosis, restoring MMP, reducing the activation of caspase-3, lessening the phosphorylation of Akt and mTOR, and increasing the expression of ATG5 and Beclin-1.Conclusions ATS and UA regulates multiple targets, bioprocesses and signal pathways against AD pathogenesis. ATS and UA synergistically protects H2O2-induced neurotrosis by regulation of AKT/mTOR signalling.